Positive pressure – analysing the effect of the addition of non-invasive ventilation (NIV) to home airway clearance techniques (ACT) in adult cystic fibrosis (CF) patients. (May 2015) - Stanford, Gemma; Parrott, Helen; Bilton, Diana; Agent, Penny
Abstract Background: There is no published literature on the frequency of use of non-invasive ventilation (NIV) with airway clearance techniques (ACT) throughout the cystic fibrosis (CF) population; 3.9% (191 people of 5062 registered) of the United Kingdom CF population older than 16 years are reported to use NIV in registry data; however, it is not specified if this is for ACT or respiratory failure. Using NIV with ACT decreases work of breathing and fatigue during in-patient admissions for CF patients. We hypothesised these effects could be replicated at home, potentially reducing hospital admissions. Method: Fourteen adult patients with CF scored ease of clearance and breathlessness with ACT before and after addition of NIV to normal ACT routine using a visual analog scale. Patient views on NIV with ACT were collected via a structured interview. Number of home intravenous (IV) antibiotic courses and days in hospital was collected for one year pre- and post-NIV provision. Results: Patients reported statistically significant improvements in ease of clearance (p = 0.011) and reduced breathlessness during ACT using NIV (p = 0.011). Structured interview results indicated patient reports of sputum clearance improved. In-patient days were lower, while home IV days were higher after NIV was set up, although not statistically significant. Conclusion: This study is limited by small numbers; however, trends towards less hospital admissions and greater patient ease while using NIV with ACT warrant further investigation.